English word-formation types in Croatian - Fabijanić, Ivo (ELOPE (Ljubljana), 2017)
The influx of Anglicisms is no longer limited to simple and open-class words in a lexicon, but it is also open to complex words and multiword expressions (e.g., phraseological units and simple sentences). Complex words are not only borrowed with their original English affixes (prefixes), but can also be formed with the addition of bound morphemes from the recipient language. This paper aims to shed more light on current Anglicisms in terms of noun phrase formation and adaptation from economic terminology into the Croatian language. It presents the results of transmorphemisation within a three-degree adaptational framework: zero, partial/compromise and complete transmorphemisation. Each adaptational degree is exemplified by English models and Croatian replicas, all described and explained in these terms. For the sake of comparison, illustration and the applicability of the model, some examples of noun phrases found in Russian, Slovene and Serbian are also provided.
Keywords: adaptacija; angleščina; anglicizmi; Croatian; English; hrvaščina; kompromisna in popolna transmorfemizacija; ničta; samostalniške besedne zveze